A relação trabalho e conhecimento nos programas de educação para o trabalho da LBA no Amapá - Carvalho, João Wilson Savino (1993)
LBA is a national institution historically connected to the governmental political organization of social actions. This institution have been appling considerable volume of recourse for many decades in the implement of programs as education to the work. LBA can be extinguished because its results are despicable. This institution characterizes by the real sense of the existence of the programs those motivate and lead the fundamental objective of this work. The answer is introduced in a way of a diagnosis of the connection between work and knowledge in the imaginary institutes of the Amapá's LBA, which is structured from the language analyses made in the official documents of the institution. It is contexted historically through a methodology hermeneutic-dialectics, which is composed which the people speech who live the practice of education to the work of the Amapá's LBA.